2003
DOI: 10.1542/peds.111.6.e714
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Safety in Pediatric Patients: A Prospective, Multicenter, Comparative Cohort Study in France

Abstract: The rates of PAEs and musculoskeletal PAEs were higher for the FQ group than the control group. This observation supports the American Academy of Pediatrics statement restricting off-label FQ use in pediatric patients to second-line treatment in a limited number of situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 35 publications
3
60
1
Order By: Relevance
“…This is similar to previous studies on AOM treatment failure that indicate 40 or 55% of S. pneumoniae isolates were multidrug-resistant [18,24]. Many authors have reported that a large proportion of AOM is caused by multidrugresistant S. pneumoniae strains [11,12,23].…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to previous studies on AOM treatment failure that indicate 40 or 55% of S. pneumoniae isolates were multidrug-resistant [18,24]. Many authors have reported that a large proportion of AOM is caused by multidrugresistant S. pneumoniae strains [11,12,23].…”
Section: Discussionsupporting
confidence: 90%
“…Resistance to cotrimoxazole and chloramphenicol were more than 50z; however, most strains were susceptible to cefoperazone/sulbactam and imipenem (96.6z and 100z, respectively). Although 81z of strains were susceptible to ciprofloxacin, the use of quinolones is limited in pediatric patients because of musculoskeletal antibiotic-associated potential adverse events (26). The rate of multiple-drug resistance (MDR) EPEC in our samples was 58.6z, lower than that in a previous report (16).…”
Section: Discussioncontrasting
confidence: 62%
“…The pediatric usages of fluoroquinolones have been restricted because there were some concerns such as risk of arthropathy for the use of quinolones in children. However, the recent reports say the safety profile of fluoroquinolones in children is not substantially different from that of adults, and these types of drugs in the treatment of otolaryngology infections in children were effective [32][33][34]. It might be possible that any extension of the indications of off-label use of fluoroquinolones in pediatric patients would be given after large clinical trials in children, although Sazawal et al [35] concluded in their report that quinolone should be continued as the second-line drugs to treat children, only after failure of an early treatment.…”
Section: Discussionmentioning
confidence: 99%